Titans. The complete first season [videorecording (DVD)] - Goldsman, Akiva (Warner Bros. Entertainment Inc., 2019)
Dick Grayson, bitter from a falling-out with Batman, emerges from the shadows to become the leader of a fearless band of new heroes including Starfire, Raven, and Beast Boy.